Adhesives in the footwear industry - Rosa M. M. Paiva (2016)
Footwear manufacturing is basically a process of transformation and assembly of various components made up of several materials where different adhesives play a key role, because without them, the shoe would lack shape and structure. This paper aims to understand the importance of adhesives in the footwear industry. It is necessary to identify the different processes in a shoemaking where adhesives are involved and the different adhesive joints produced, as well as their technical requirements. The adhesive joint performance will depend on the different adherends' nature used as footwear materials, the joint design, the surface treatments, the adhesive properties which depend on their formulation, and so on. Adhesive joints in a shoe act under different stress types (peel, shear, tensile, etc.). The most disfavourable are the peel stress. For that reason, the peel strength test is one of the most common to evaluate adhesive joints' performance. When heat resistance is an important adhesive requirements, a creep test is carried out. Furthermore, aging tests are undertaken in order to evaluate durability. This methodology is described in this paper. In the literature, one can find several papers on adhesives, specifically on their mechanical properties. However, there is little research related to footwear applications, including not only the mechanical properties that this industry demands, but also the composition of the adhesives. Therefore, this paper aims to connect the important mechanical properties for the footwear industry with the constituents of the adhesives. However, other properties are also important, such as viscosity, wettability, compatibility, etc., depending on the materials and the adhesive joint type.